A modeling method for a disaster chain–Taking the coal mining subsidence chain as an example. Issue 5 (4th July 2018) - Chen, Yuejuan; Zhang, Jin; Zhou, Anchao; Yin, Bo
ABSTRACT: The research of a disaster chain can help to determine the mechanism of disaster and the mechanism of mutual transformation between disasters; but at present, a unified and comprehensive modeling mechanism for the disaster chain evolution process has not been formed. Based on hierarchical modeling theory, a top-down refinement method for modeling the complex disaster chain evolution process was proposed in this article—the Spatio-temporal evolution process Multi-level description Framework for a Disaster Chain (STMFDC). The semantic description of the disaster chain is realized at the phenomenon level, changing element level, abstract semantics association level, and resource implementation level. In the spatio-temporal semantic constraint, combining the data integration methods, the evolution process model was also built to analyze the catastrophic process of the disaster chain. Finally, the mining subsidence disaster chain caused by human engineering activity was taken as an example to analyze the evolution process of a subsidence disaster chain based on the STMFDC to verify its generality. The study will thus form a new way of researching a disaster chain by building off the STMFDC approach.